Immigration and Right-Wing Populism: Evidence from a Natural Experiment - Adrian Mehic (Lund University, School of Economics and Management, Department of Economics, 2019)
Between the 2014 and 2018 Swedish parliamentary elections, the vote share of the anti-immigration Sweden Democrats increased significantly. To evaluate the possibility of a causal link between immigration and the right-wing populist vote, this paper uses data from a nationwide policy experiment, under which refugees are allocated randomly to every municipality in the country, creating exogenous variation in the number of refugees between municipalities. Overall, I find a positive and significant impact of immigration on the anti-immigration vote. In areas with strong anti-immigration sentiments during the 1990s refugee wave, the effect is magnified significantly. However, when considering immigration of a particular refugee group dominated by young men, the relationship is considerably weaker. I show that this is because immigration of young men has a balancing effect on the right-wing populist vote among immigration-friendly voter groups.
Keywords: D72; J15; P16; 330; immigration; right-wing populism; natural experiment